Upaya Meningkatkan Hasil Belajar Siswa melalui Model Pembelajaran Discovery Learning pada Mata Pelajaran IPA Kelas VIII di SMPN 10 Padang - Sari, Gita Widya; Putri, Rahmah Evita; Yenira, Fitria (Lembaga Yasin AlSys, 2025)
Science instruction in Class VIII.8 at SMPN 10 Padang demonstrates the need to improve student learning outcomes through the implementation of more effective methods. This study aims to enhance student achievement by applying the Discovery Learning model. The research employed a Classroom Action Research (Penelitian Tindakan Kelas) design conducted in two cycles, involving 30 students during the Field Teaching Practice (Praktik Pengalaman Lapangan/PPL) 2 in the 2024/2025 academic year. The procedure followed Lewin’s action research cycle model, consisting of planning, action, observation, and reflection stages. Data were collected through student activity observations, field notes, and multiple-choice tests administered as pretests and posttests, and analyzed using percentage formulas for both individual and class-wide mastery. The results revealed a significant improvement in learning outcomes, with mastery rising from 33.33% in the pre-cycle to 43.33% in the first cycle, and then sharply increasing to 86.67% in the second cycle after refining the instructional strategy. These findings demonstrate that the Discovery Learning model is effective in improving science learning outcomes by promoting active engagement, conceptual exploration, and deeper understanding throughout the learning process.